Promiscuity and Adolescent Morality in Rural: A Study of Teenagers in Mendolo Village - Latifah, Umul; Sholehuddin, M. Sugeng; Adinugraha, Hendri Hermawan (PUSAKA, 2024)
Promiscuity and the degradation of adolescent morality have become a current problem in rural and urban areas. This research describes promiscuity’s influence on teenage morality in Dukuh Mendolo Wetan, Mendolo Village, Lebakbarang District, and Pekalongan Regency. The approach used in this research is quantitative. This approach is used to produce data obtained from teenagers, which is then presented, and conclusions will be made in the form of numbers. This research was conducted in the Dukuh Mendolo Wetan environment, Mendolo Village, Lebakbarang District, Pekalongan Regency. The population in this research were teenagers in Dukuh Mendolo Wetan, Mendolo Village, Lebakbarang District, Pekalongan Regency, aged 12 to 18 years, totaling 30 children. The sampling technique used was saturated sampling, in which the researcher took the entire population as the research sample. The data collection technique used in this research is the questionnaire method. The steps for this research data analysis technique are scoring technique, validity test and reliability test analysis, data analysis prerequisite test, and hypothesis test analysis. This research concludes that the variable of promiscuity has a significant effect on the variable of adolescent morality in Dukuh Mendolo Wetan, Mendolo Village, Lebakbarang District, Pekalongan Regency. The magnitude of the influence of promiscuity on adolescent morality is 98.7%, while other factors influence 1.3%. The findings of this research show that if parents and society can control promiscuity, then automatically, the morality of teenagers in Mendolo Village will also improve and vice versa.